Analysis of Need for Teaching Materials Based STEM-PjBL Assisted by Instructional Videos on Topic Voltaic Cells : Analisis Kebutuhan Bahan Ajar Berbasis STEM-PjBL Berbantuan Video Pembelajaran Pada Topik Sel Volta - Rokhim, Deni Ainur; Syafruddin, Afis Baghiz; Widarti, Hayuni Retno (Universitas Muhammadiyah Sidoarjo, 2020)
In the era of the ASEAN Economic Community (AEC), Indonesia was led to prepare competitive, skilled and expert human resources so that they could compete with other countries. Therefore, the preparation of teaching materials is ideal for optimizing the involvement of students in the learning process of chemistry especially the famous abstract voltaic cell material. The low ability of students to think formally leads to difficulty understanding submicroscopic aspects so that there is the potential for misunderstanding on the topic of this voltaic cell. The purpose of this study is to explain the analysis of the needs in the development of teaching materials on the topic of STEM-PjBL-based voltaic cells assisted with learning videos. This type of research is used descriptive research with open and closed questionnaire techniques. The results of the study found that teachers and students still use conventional teaching materials that have not been integrated with approaches and methods. In addition, these teaching materials have not used information and communication technology that is more in demand by students. Thus it can be seen that overall the development of voltaic cell textbooks based on specific approaches and methods is still needed with integrated information and communication technology.